Rhetoric and law in early modern Europe - Kahn, Victoria Ann; Hutson, Lorna (Yale University Press, 2001)
"The book provides a historical perspective on such issues as the role of contract law in the production of the modern subject, the intersection of rhetoric and law in the construction of gender and sexuality, and the contribution of theories of equity to early modern notions of intention and political agency. The essays also shed light on the influence of legal decisions on early modern values in public and private life, on notions of literary fiction, and on ideas about the social contract."--Jacket